1996
DOI: 10.1007/s002239900129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-Ray Irradiation on Proliferation and Differentiation of Osteoblast

Abstract: We exposed the osteoblast-like cell line, MC3T3-E1, to 1-to 10-Gy X-ray. Irradiation at doses of 5-Gy dose or stage, confluence, and post-proliferation stages. The alkaline phosphatase activity, conversely, was increased by irradiation, and the calcium content of irradiated cells was greater than that of nonirradiated. These findings suggest that irradiation induces terminal differentiation and calcification of osteoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 0 publications
5
38
2
Order By: Relevance
“…These results agree with those of Arnold et al on irradiated bone [23]. Spontaneous bone repair is highly compromised and reduced in irradiated areas and the physiology of bone repair is modified after radiation therapy [21,[24][25][26]. Ionizing radiation delays fracture union, increases the incidence of fibrous union [26], induces osteoradionecrosis [7] and adversely reduces the quality of bone grafts [8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results agree with those of Arnold et al on irradiated bone [23]. Spontaneous bone repair is highly compromised and reduced in irradiated areas and the physiology of bone repair is modified after radiation therapy [21,[24][25][26]. Ionizing radiation delays fracture union, increases the incidence of fibrous union [26], induces osteoradionecrosis [7] and adversely reduces the quality of bone grafts [8].…”
Section: Discussionsupporting
confidence: 87%
“…Ionizing radiation delays fracture union, increases the incidence of fibrous union [26], induces osteoradionecrosis [7] and adversely reduces the quality of bone grafts [8]. The compromised features of irradiated bone repair are due to the cellular effects of ionizing radiation; osteoblasts and osteoclasts are quantitatively decreased with radiotherapy [24,25]; terminal differentiation of osteoblasts is accelerated [24]. Marrow stroma is also damaged by radiation exposure [27].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of DNA synthesis were measured by [methyl- 3 H] thymidine deoxyribose (TdR; Amersham Pharmacia Biotech Inc., Piscataway, NJ, USA) incorporation assay. In brief, cells grown in 96-multiwell plates were treated with 1 μCi TdR/well at 3 days post-irradiation and then processed for an additional 12 h incubation.…”
Section: Measurement Of Dna Synthesismentioning
confidence: 99%
“…Numerous studies have attempted to determine the mechanisms by which irradiation affects bone differentiation and mineralization. Considerable findings have shown that irradiation leads to detrimental effects on cells, as evidenced by decreased viability and/or DNA synthesis in bone-like (3)(4)(5), leukemia (6), and mesenchymal stromal cells (7). Irradiation also results in single or double-stranded DNA breaks and eventually blocks cell cycle progression (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation